Setting new behavioural standards: Sustainabilty pledges and how conformity impacts their outreach - Ann-Kathrin Koessler (ZBW – Leibniz Information Centre for Economics, 2019)
Sustainability pledges are en vogue. In the business sector, but also in climate negotiations, pledges are used to signal actors' intention to act pro-environmentally. Laboratory experiments testify to the potential effectiveness of these public declarations. Previous work has examined under which conditions subsequent trust and cooperation can flourish. In this study, I postulate that also conformity is an important determinant for the effectiveness of pledges. In specific, I examine what role social influence plays in the decision to pledge. In a public good game, subjects can make prior play a pledge to contribute to the public good in the socially optimal way. Across treatment conditions, I vary the way in which the pledges are elicited. Hence, the degree of social influence on pledge making is manipulated and its impact can be examined. I find that when individuals are aware that the majority of other subjects decided to pledge, they are likely to conform and also make the pledge. The emergence of such a critical mass can be stimulated when the elicitation of pledges is based on previous contribution behavior. Overall, this commitment nudge is effective. Both socially-oriented and previously not socially-oriented subjects modify their behavior after the pledge.
Keywords: A13; C72; C91; H41; 330; voluntary approaches; environmental policy; pledge; social dilemma; public good; commitment; conformism